Proceedings of the 2013 Workshop on Data Driven Functional Programming 2013
DOI: 10.1145/2429376.2429379
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic data types for language-integrated queries

Abstract: The seamless integration of relational databases and programming languages remains a major challenge. Mapping rich data types featured in general-purpose programming languages to the relational data model is one aspect of this challenge. We present a novel technique for mapping arbitrary (nonrecursive) algebraic data types to a relational data model, based on previous work on the relational representation of nested tables. Algebraic data types may be freely constructed and deconstructed in queries and may show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Giorgidze et al [22] have shown how to support non-recursive datatypes (i.e. sums) and Grust and Ulrich [29] built on this to show how to support function types in query results using defunctionalization [29].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Giorgidze et al [22] have shown how to support non-recursive datatypes (i.e. sums) and Grust and Ulrich [29] built on this to show how to support function types in query results using defunctionalization [29].…”
Section: Related Workmentioning
confidence: 99%
“…sums) and Grust and Ulrich [29] built on this to show how to support function types in query results using defunctionalization [29]. We considered using sums to support a defunctionalization-style strategy for query lifting, but Giorgidze et al [22] map sum types to nested collections, which makes their approach unsuitable to our setting. Wong's original normalization result also considered sum types, but to the best of our knowledge normalization for N RC λ (Set, Bag) extended with sum types has not yet been proved.…”
Section: Related Workmentioning
confidence: 99%
“…To implement expression provenance in L T we would need to find a suitable (nested) relational encoding. Giorgidze et al [2013] show how to encode arbitrary nonrecursive algebraic datatypes relationally and use this in an extension to the language-integrated query library D . The datatype for expressions is recursive, but of a limited depth and thus can be unrolled.…”
Section: Other Forms Of Provenancementioning
confidence: 99%
“…Crary et al [2002] introduce λ r , a variant of λ ML i where runtime type information is explicitly represented as a datatype when necessary. Giorgidze et al [2013] show how to translate algebraic datatypes to S and translate functions to S . It seems plausible that one could put these together to translate all of L T to S without necessarily normalizing to eliminate functions, traces, and typecase.…”
Section: Related and Future Workmentioning
confidence: 99%
“…While this model appears to generalize all of the aforementioned approaches, it appears nontrivial to implement by translation to relational queries, because it is not obvious how to represent the traces in this approach in a relational data model. (Giorgidze et al [2013] show how to support nonrecursive algebraic data types in queries, but the trace datatype is recursive.) This would be a challenging area for future work.…”
Section: Related Workmentioning
confidence: 99%